PEMBINAAN AKHLAK PADA ANAK USIA DINI MELALUI METODE PEMBIASAAN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Muhammad Ibnu Faruk Fauzi (Pusat Riset dan Inovasi Nasional, 2022)
Habituation in education is very much needed because psychologically, students model more behavior or figures they idolize, including their teachers. Habituation is also no less important in learning activities. This is because any knowledge or behavior gained by habituation will be very difficult to change or eliminate it so that this method is very useful in educating children. Moral development activities for students are carried out at Dharma Wanita Sumberrejo Kindergarten through the habituation method of learning Islamic Religious Education (PAI). The research method used is a service method that describes the phenomenon that occurs as it is, data sources are obtained through school leaders, teachers and parents of children. The analysis is carried out with reference to the stages of tabulation, coding and giving meaning to the data. The results of the service show that the implementation of child moral development through the habituation method already contains the main teachings of Islam, namely Akidah (faith), Sharia (Islamic) and Akhlak (Ihsan). The method of habituation given by means of getting used to the behavior or moral attitude of the child repeatedly and continuously. In addition to the habituation carried out by teachers in schools, the role of parents is actually important for children's habituation in practicing Islamic teachings that have been taught through habituation in schools, but this role will not be maximized when parental involvement is not full on the development of children's behavior and morals.